The IFS Green Budget: October 2018 - Ben Zaranko; Christine Farquharson; Paul Johnson (Institute for Fiscal Studies (IFS), 2018)
The IFS Green Budget 2018, in association with Citi, ICAEW and the Nuffield Foundation, is edited by Carl Emmerson, Christine Farquharson and Paul Johnson, and copy-edited by Judith Payne. The report looks at the issues and challenges facing Chancellor Philip Hammond as he prepares for his Budget later in October.
Keywords: 330; Öffentlicher Haushalt; Finanzpolitik; Steuerpolitik; Großbritannien